Catalyst for catalytic reduction of NOx as well as preparation method and application of catalyst

Through the design of PrW-Ce/SiO2-TiO2 composite oxide catalyst, combined with amino modification and acid introduction, the problems of poor low-temperature activity, high cost and poor high-temperature thermal stability are solved, and high efficiency is achieved in a wide range. NOx removal effect.

CN119303563AActive Publication Date: 2025-01-14WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411414139.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-14
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

The existing NOx removal catalysts have poor activity, high cost, poor thermal stability and selectivity at low temperatures, which are easy to generate by-product N2O, and have poor water resistance, so they cannot effectively adapt to different working conditions.

Method used

Using PrW-Ce/SiO2-TiO2 composite oxide catalyst, the acidic sites are increased through the synergistic action of Pr and W, the adsorption and activation of NH3 are promoted, and the dispersion of active components is increased, and the activity window of catalyst is broadened, and the core-shell structure is formed. Increase the surface area, combine amino modification and acid introduction to form active sites, and enhance NOx adsorption and reaction rates.

Benefits of technology

Maintain high catalytic activity in the range of 100℃-600℃, improve low-temperature denitrification performance, improve anti-toxic inactivation performance, solve the problems of narrow temperature windows and poor water resistance, and achieve efficient and stable NOx removal.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005078887920000091
    Figure BDA0005078887920000091
Patent Text Reader

Abstract

The invention discloses a catalyst for catalytic reduction of NOx as well as a preparation method and application of the catalyst. CeO2 is used as the main active component, Pr2O3 and WO3 are used as the auxiliaries, SiO2 and TiO2 are used as the carriers, a hydrothermal method is adopted for preparation, and the amino groups are inoculated for surface modification. The catalyst provided by the invention has relatively high NOx removal capability. Meanwhile, the auxiliaries Pr, W and Ce, amino groups and surface defects can play a very good synergistic catalysis role, so that the anti-poisoning performance of the catalyst is enhanced, and the active catalytic temperature window of the catalyst is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst for removing NOx, belonging to the fields of air pollution control technology and environmental catalysis. Background Art

[0002] Nitrogen oxides (NOx) are one of the main pollutants in the atmosphere and one of the main causes of haze, photochemical smog, greenhouse effect and acid rain. They mainly include NO, NO2 and N2O, among which NO accounts for more than 90%. In addition, NOx can also harm human health. Therefore, the emission of NOx must be controlled. The technology of efficient removal of NOx is of great value and has become a current research hotspot. At present, ammonia selective catalytic reduction (NH3-SCR) is regarded as the most common, mature and efficient technology in the field of denitrification. This technology can effectively convert NOx into harmless N2 and H2O within the appropriate temperature range of the catalyst, and can reduce NOx emissions by more than 90%.

[0003] Catalysts are the core of the selective catalytic reduction process, which can remove nitrogen oxides efficiently and selectively. SCR catalysts can be roughly divided into precious metal catalysts, transition metal oxide catalysts, molecular sieve catalysts, and activated carbon catalysts. Among them, metal oxide catalysts are widely used in NOx removal processes due to their excellent catalytic activity, high material stability and controllability, and relatively low prices. Transition metal oxides are a type of catalyst that is simple to prepare, abundant in resources, and much cheaper than precious metals. V2O5-WO3 / TiO2 catalysts have been widely used commercially, but this catalyst still has some disadvantages in practical applications, such as narrow catalytic temperature window, low N2 selectivity, poor water resistance, and high-temperature NH3 overoxidation. Therefore, a new type of NOx removal catalyst is needed to be suitable for removing NOx under different conditions.

[0004] Modifying and grafting groups on the catalyst is an effective measure to improve the catalytic performance of the catalyst. Preparing a core-shell structure is a way to solve the problem of catalyst poisoning. These modification methods can greatly improve the overall catalytic activity and poisoning resistance of the catalyst. Therefore, by further increasing the contact area between the NOx-containing exhaust gas and the catalyst surface, while promoting the adsorption and mass transfer of surfactants, strengthening this performance can effectively achieve further improvement in catalytic NOx removal performance.

[0005] At present, China has conducted a lot of research on non-vanadium-titanium-based denitrification catalysts, such as a NOx removal catalyst disclosed in patent CN112452321A, which has good performance in the temperature window of 150-500°C, but the catalytic effect is significantly reduced at low temperatures. For example, a molecular sieve catalyst disclosed in patent CN116510774A has a significantly reduced catalytic effect at low temperatures, and the preparation cost of the catalyst is high, and the thermal stability of long-term operation at high temperatures is poor. For example, a molecular sieve catalyst disclosed in patent CN106111183A has a significantly reduced catalytic effect at low temperatures. The denitrification catalysts in the prior art have certain problems, including poor activity at low temperatures, high cost, poor thermal stability and selectivity at high temperatures, and easy generation of by-product N2O. Summary of the invention

[0006] In view of the problems existing in the existing technology, the present invention provides a catalyst for catalytic reduction of NOx and its preparation method and use. The catalyst of the present invention is a PrW-Ce / SiO2-TiO2 composite oxide. The synergistic effect between W and Ce increases the acid sites on the catalyst surface, promotes the adsorption and activation of NH3 species in the gas, and improves the reaction activity of the adsorbed NH3 species; adding a small amount of auxiliary agent Pr can not only promote the high dispersion of active components but also strengthen the interaction between the auxiliary agent and the active components and the carrier, and improve the low-temperature denitrification activity of the catalyst; in addition, due to the synergistic effect between Pr and W, while broadening the catalyst activity window, the anti-poisoning and inactivation performance of the catalyst in the presence of H2O is improved; the core-shell structure increases the specific surface area of ​​the catalyst, promotes the adsorption and mass transfer of surface active substances; the surface defects of cerium oxide make it have rich active oxygen and oxygen storage and release capacity, promote the conversion of NO into NO2, and make it proceed to the path of rapid SCR catalytic reaction. By grafting amino groups onto the catalyst surface and adding acid, the surface defects and oxygen free radicals of the catalyst are increased, more active sites are formed, and the adsorption and reaction rate of the catalyst to NOx are enhanced, thereby producing a catalyst with good NOx removal performance.

[0007] The preparation process is simple, the obtained catalyst has good stability, high selectivity, and good catalytic activity and anti-poisoning characteristics in the entire catalytic activity range, which can solve the problems of narrow active temperature window and poor water resistance of denitrification catalysts in the prior art. The catalyst can be used to eliminate NOx emissions from fixed sources such as thermal power plants and industrial boilers, as well as mobile sources such as diesel vehicles.

[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0009] A catalyst for catalytic reduction of NOx, comprising the following components:

[0010] Carrier: core-shell structure SiO2-TiO2,

[0011] Active ingredients: CeO2,

[0012] Additives: Pr2O3 and WO3,

[0013] Amino groups modified on the catalyst surface;

[0014] Based on the mass of the carrier, the mass percentage of CeO2 is 4%-20%, the mass percentage of Pr2O3 is 1%-5%, and the mass percentage of WO3 is 1%-5%; the molar ratio of Ti to Si is 1-5.

[0015] The present invention provides a method for preparing the catalyst, comprising the following steps:

[0016] (1) uniformly mixing a dispersant, a solvent and an alkali solution, adding a silicon source, filtering, washing and drying to obtain silicon nanocores;

[0017] (2) grinding the silicon nanocore into powder, adding it to a mixed solution of a solvent and an alkali solution, then adding a titanium source, keeping the mixture warm, filtering, washing, drying, and calcining to obtain a core-shell structure carrier;

[0018] (3) grinding the core-shell structure carrier into powder, adding the precursor solution of the active component, and drying to obtain a core-shell catalyst loaded with the active component;

[0019] (4) grinding the core-shell catalyst loaded with active components into powder, adding the precursor solution of the auxiliary component, drying, and calcining;

[0020] (5) Grinding the product obtained in step (4) into powder, adding it to a mixed solution containing an organic ligand with an amino group, an organic solvent, and an acid, filtering it with suction, washing it, drying it, and calcining it.

[0021] Furthermore, the dispersant in step (1) includes one or more of cetyltrimethylammonium bromide (CTAB), P123, and polyethylene glycol.

[0022] Furthermore, the solvent in step (1) includes ethanol and / or water.

[0023] Furthermore, the alkali solution in step (1) is selected from one or more of urea, ammonia water, and tetramethylammonium hydroxide.

[0024] Furthermore, the silicon source in step (1) is selected from one or more of ethyl orthosilicate, methyl orthosilicate, silicon tetrachloride and silicic acid.

[0025] Furthermore, in step (1), the mass ratio of the dispersant to the silicon source is 1:1 to 3.

[0026] Furthermore, in step (1), stirring is used to mix evenly, and the stirring time is 4-10 hours.

[0027] Furthermore, the washing in step (1) is washing with ethanol and water respectively in sequence until the pH is 7.

[0028] Furthermore, in step (1), the drying temperature is 80-120° C., and the drying time is 10-14 h.

[0029] Furthermore, the solvent in step (2) is ethanol and / or water.

[0030] Furthermore, the alkaline solution in step (2) is selected from one or more of urea, ammonia water, and tetramethylammonium hydroxide.

[0031] Furthermore, the titanium source in step (2) is selected from tetrabutyl titanate and / or titanium tetrachloride.

[0032] Furthermore, in step (2), the material mixing is carried out in the form of stirring, and the stirring time is 4-10 hours.

[0033] Furthermore, the insulation temperature in step (2) is 100-200°C.

[0034] Furthermore, the insulation time in step (2) is 10-24 hours.

[0035] Furthermore, the washing in step (2) is washing with ethanol and water respectively in sequence until the pH is 7.

[0036] Furthermore, in step (2), the drying temperature is 80-120° C., and the drying time is 10-14 h.

[0037] Furthermore, in step (2), the calcination temperature is 200-600° C., and the calcination time is 2-6 hours.

[0038] Furthermore, the precursor solution of the active component in step (3) is a nitrate solution thereof.

[0039] Furthermore, in step (3), the material mixing is carried out in the form of stirring, and the stirring time is 4-10 hours.

[0040] Furthermore, in step (3), the drying temperature is 80-120° C., and the drying time is 10-14 h.

[0041] Furthermore, the precursor solution of the auxiliary agent component in step (4) is a nitrate solution thereof.

[0042] Furthermore, in step (4), the material mixing is carried out in the form of stirring, and the stirring time is 4-10 hours.

[0043] Furthermore, in step (4), the drying temperature is 80-120° C., and the drying time is 10-14 h.

[0044] Furthermore, in step (4), the calcination temperature is 200-600° C., and the calcination time is 2-6 hours.

[0045] Furthermore, in step (5), the organic ligand with an amino group is selected from one or more of 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 2-amino-4,4'-biphenyldicarboxylic acid, ethylenediamine, and phenylenediamine.

[0046] Furthermore, in step (5), the organic solvent is selected from one or more of DMF, ethanol and water.

[0047] Furthermore, in step (5), the acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and formic acid.

[0048] Furthermore, the washing in step (5) is washing with ethanol and water respectively in sequence until the pH is 7.

[0049] Furthermore, in step (5), the drying temperature is 80-120° C., and the drying time is 10-14 h.

[0050] Furthermore, in step (5), the calcination temperature is 200-600° C., and the calcination time is 2-6 hours.

[0051] Furthermore, in step (5), the mass volume ratio of the product obtained in step (4) to the organic ligand with amino group is 1 g: 2-4 ml, the volume ratio of the organic ligand with amino group to the organic solvent is 1: 1-2, and the volume ratio of the organic ligand with amino group to the acid is 1: 1-3.

[0052] A method for removing NOx, comprising the following steps: 10-1000ppm NO, 10-1000ppm NH3, 10% H2O, and the rest air, with a gas flow rate of 300ml / min and a gas space velocity of 100000-180000h -1 , the concentration ratio of NO to NH3 is 1: 1. KM-9106 flue gas analyzer and Fourier transform infrared spectrometer are used to analyze gas concentration online, and the reactor is a fixed bed reactor.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) The synergistic effect between the carrier and the active component enables it to have excellent redox performance, electron transfer ability and surface acidic sites. The core-shell structured nanomaterials have a high specific surface area and large pore volume, and can instantly and efficiently adsorb the target gases NOx and NH3.

[0055] (2) The present invention grafts amino groups onto the catalyst surface and simultaneously introduces acid to adjust surface defects. Due to the introduction of amino groups and defects, more active sites and oxygen free radicals are formed, the adsorption and activation effect on NOx is stronger, and the adsorption and reaction activity of the catalyst to NOx is enhanced.

[0056] (3) It is not affected by H2O during low-temperature catalysis and can maintain high catalytic efficiency for a long time without affecting the service life of the catalyst. It has good catalytic activity in the range of 100℃-600℃, showing excellent low-temperature and high-temperature denitrification performance, solving the problems of narrow temperature window, poor water resistance and easy poisoning of existing commercial catalysts. DETAILED DESCRIPTION

[0057] Example 1 (1% Pr2O33% WO3-10% CeO2 / SiO2-TiO2)

[0058] (1) Mix 20 ml of water, 100 ml of ethanol, and 30 ml of 28% wt ammonia solution, add 2 g of dispersant hexadecyltrimethylammonium bromide (CTAB), and stir at room temperature for 2 h. Add 4.7 g of tetraethyl orthosilicate to the mixed solution and stir at room temperature for 4 h. Then filter and wash with ethanol and water three times until the pH is 7, and then dry the filter cake in an oven at 110°C for 12 h to obtain silicon nanocores.

[0059] (2) Grind the silicon nanocore into powder, add it to a mixed solution of 20ml water, 100ml ethanol, and 30ml 28%wt ammonia water, and stir it at room temperature for 2h. Add 7.68g tetrabutyl titanate to the above mixed solution and stir it at room temperature for 4h. Transfer the reaction solution to a stainless steel reactor lined with polytetrafluoroethylene and keep it at 160℃ for 24h. After the insulation is completed and the temperature drops to room temperature, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110℃ for 12h, and then calcine it at 500℃ in a muffle furnace for 4h (heating rate 2℃ / min), and obtain a core-shell structure carrier with a mol ratio of SiO2 to TiO2 of 1:2.

[0060] (3) 2 g of the above carrier was ground into powder, added to 7.26 ml of 0.16 mol / l cerium nitrate solution, stirred at room temperature for 4 h, and then dried in an oven at 110° C. for 12 h to obtain a catalyst loaded with active components.

[0061] (4) Grind 2 g of the above carrier into powder, add it to 2.16 ml of 0.01 mol / l ammonium metatungstate solution and 3.03 ml of 0.04 mol / l praseodymium nitrate solution, stir it at room temperature for 4 h, dry it in an oven at 110 °C for 12 h, and then calcine it at 200 °C for 2 h and 500 °C for 4 h in a muffle furnace (heating rate 2 °C / min) to obtain the supported catalyst.

[0062] (5) Grind 2 g of the above carrier into powder, add it to a mixed solution of 5 ml of 3-aminopropyltrimethoxysilane, 6 ml of DMF, and 8 ml of nitric acid, stir it at room temperature for 4 h, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110 ° C for 12 h, and then calcine it at 200 ° C for 2 h and 400 ° C for 2 h in a muffle furnace (heating rate 2 ° C / min) to obtain the final amino-modified core-shell catalyst.

[0063] Test conditions: 500ppm NO, 500ppm NH3, H2O 10%, the rest is air, gas flow rate is 300ml / min, gas space velocity is 150000h -1 , the concentration ratio of NO and NH3 is 1:1.

[0064] Example 2 (3% Pr2O31% WO3-10% CeO2 / SiO2-TiO2)

[0065] (1) Mix 20 ml of water, 100 ml of ethanol, and 30 ml of 28% wt ammonia solution, add 5 g of dispersant hexadecyltrimethylammonium bromide (CTAB), and stir at room temperature for 2 h. Add 9.2 ml of methyl orthosilicate to the mixed solution and stir at room temperature for 4 h. Then filter and wash with ethanol and water three times until the pH is 7, and then dry the filter cake in an oven at 110°C for 12 h to obtain silicon nanocores.

[0066] (2) Grind the silicon nanocore into powder, add it to a solution of 20 ml water, 100 ml ethanol, and 30 ml 28% wt ammonia water, and stir it at room temperature for 2 hours. Add 4.66 g titanium tetrachloride to the above mixed solution and stir it at room temperature for 4 hours. Transfer the reaction solution to a stainless steel reactor lined with polytetrafluoroethylene and keep it at 180°C for 24 hours. After the insulation is completed and the temperature drops to room temperature, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110°C for 12 hours, and then calcine it at 500°C in a muffle furnace for 4 hours (heating rate 2°C / min), and a core-shell structure carrier is obtained, and the mol ratio of SiO2 to TiO2 is 2:1.

[0067] (3) 2 g of the above carrier was ground into powder, added to 7.2 ml of 0.16 mol / l cerium nitrate solution, stirred at room temperature for 4 h, and then dried in an oven at 110° C. for 12 h to obtain a catalyst loaded with active components.

[0068] (4) Grind 2g of the above carrier into powder, add it into 0.72ml 0.01mol / l ammonium metatungstate solution and 9.1ml 0.04mol / l praseodymium nitrate solution, stir it at room temperature for 4h, dry it in an oven at 110℃ for 12h, and then calcine it in a muffle furnace at 200℃ for 2h and 400℃ for 2h (heating rate 2℃ / min). The supported catalyst is obtained.

[0069] (5) Grind 2 g of the above carrier into powder, add it to a mixed solution of 7 ml of 2-amino-4,4'-biphenyldicarboxylic acid, 7.2 ml of DMF, and 8.7 ml of hydrochloric acid, stir it at room temperature for 4 h, filter it, wash it with ethanol and water three times until the pH is 7, dry the filter cake in an oven at 110 ° C for 12 h, and then calcine it at 200 ° C for 2 h and 400 ° C for 2 h in a muffle furnace (heating rate 2 ° C / min) to obtain the final amino-modified core-shell catalyst.

[0070] The test conditions are: 500ppm NO, 500ppm NH3, H2O 10%, the rest is air, the gas flow rate is 300ml / min, the gas space velocity is 150000h -1 , the concentration ratio of NO and NH3 is 1:1.

[0071] Example 3 (3% Pr2O33% WO3-12% CeO2 / SiO2-TiO2)

[0072] (1) 20 ml of water, 100 ml of ethanol, and 30 ml of 28% wt ammonia solution were mixed, 3.85 g of dispersant poly P123 was added, and the mixture was stirred at room temperature for 2 h. 9.4 g of tetraethyl orthosilicate was added to the mixed solution, and the mixture was stirred at room temperature for 4 h. The mixture was then filtered, washed with ethanol and water for 3 times until the pH value was 7, and the filter cake was dried in an oven at 110°C for 12 h to obtain silicon nanocores.

[0073] (2) Grind the silicon nanocore into powder, add it to a solution of 20 ml water, 100 ml ethanol, and 30 ml 28% wt ammonia water, and stir it at room temperature for 2 hours. Add 5.12 g of tetrabutyl titanate to the above mixed solution and stir it at room temperature for 4 hours. Transfer the reaction solution to a stainless steel reactor lined with polytetrafluoroethylene and keep it at 200°C for 24 hours. After the insulation is completed and the temperature drops to room temperature, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110°C for 12 hours, and then calcine it at 500°C in a muffle furnace for 4 hours (heating rate 2°C / min), and a core-shell structure carrier is obtained, and the mol ratio of SiO2 to TiO2 is 3:1.

[0074] (3) 2 g of the above carrier was ground into powder, added to 8.72 ml of 0.16 mol / l cerium nitrate solution, stirred at room temperature for 4 h, and then dried in an oven at 110° C. for 12 h to obtain a catalyst loaded with active components.

[0075] (4) Grind 2g of the above carrier into powder, add it to 2.16ml 0.01mol / l ammonium metatungstate solution and 9.1ml 0.04mol / l praseodymium nitrate solution, stir it at room temperature for 4h, dry it in an oven at 110℃ for 12h, and then calcine it at 200℃ for 2h and 400℃ for 2h in a muffle furnace (heating rate 2℃ / min). The supported catalyst is obtained.

[0076] (5) Grind 2 g of the above carrier into powder, add it to a mixed solution of 6 ml of ethylenediamine, 9 ml of DMF, and 12 ml of nitric acid, stir it at room temperature for 4 h, filter it, wash it with ethanol and water three times until the pH is 7, dry the filter cake in an oven at 110 ° C for 12 h, and then calcine it at 200 ° C for 2 h and 400 ° C for 2 h in a muffle furnace (heating rate 2 ° C / min) to obtain the final amino-modified core-shell catalyst.

[0077] Test conditions: 500ppm NO, 500ppm NH3, H2O 10%, the rest is air, gas flow rate is 300ml / min, gas space velocity is 150000h -1 , the concentration ratio of NO and NH3 is 1:1.

[0078] Example 4 (1% Pr2O31% WO3-4% CeO2 / SiO2-TiO2)

[0079] (1) 20 ml of water, 100 ml of ethanol, and 30 ml of 28% wt ammonia solution were mixed, 1.71 g of dispersant P123 was added, and the mixture was stirred at room temperature for 2 h. 5.12 g of methyl orthosilicate was added to the mixed solution, and the mixture was stirred at room temperature for 4 h. The mixture was then filtered, washed with ethanol and water for 3 times until the pH value was 7, and the filter cake was dried in an oven at 110° C. for 12 h to obtain silicon nanocores.

[0080] (2) Grind the silicon nanocore into powder, add it to a solution of 20 ml water, 100 ml ethanol, and 30 ml 28% wt ammonia water, and stir it at room temperature for 2 hours. Add 8.36 g of tetrabutyl titanate to the above mixed solution and stir it at room temperature for 4 hours. Transfer the reaction solution to a stainless steel reactor lined with polytetrafluoroethylene and keep it at 160°C for 18 hours. After the insulation is completed and the temperature drops to room temperature, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110°C for 12 hours, and then calcine it at 500°C in a muffle furnace for 4 hours (heating rate 2°C / min), and a core-shell structure carrier is obtained, and the mol ratio of SiO2 to TiO2 is 1:1.

[0081] (3) 2 g of the above carrier was ground into powder, added to 2.91 ml of 0.16 mol / l cerium nitrate solution, stirred at room temperature for 4 h, and then dried in an oven at 110° C. for 12 h to obtain a catalyst loaded with active components.

[0082] (4) Grind 2g of the above carrier into powder, add it into 0.72ml 0.01mol / l ammonium metatungstate solution and 3.03ml 0.04mol / l praseodymium nitrate solution, stir it at room temperature for 4h, dry it in an oven at 110℃ for 12h, and then calcine it at 200℃ for 2h and 400℃ for 2h in a muffle furnace (heating rate 2℃ / min). The supported catalyst is obtained.

[0083] (5) Grind 2 g of the above carrier into powder, add it to a mixed solution of 4 ml of 3-aminopropyltrimethoxysilane, 4 ml of ethanol and 4 ml of hydrochloric acid, stir it at room temperature for 4 h, filter it, wash it with ethanol and water three times until the pH is 7, dry the filter cake in an oven at 110 ° C for 12 h, and then calcine it at 200 ° C for 2 h and 400 ° C for 2 h in a muffle furnace (heating rate 2 ° C / min) to obtain the final amino-modified core-shell catalyst.

[0084] Test conditions: 500ppm NO, 500ppm NH3, 10% H2O, the rest is air, gas flow rate is 300ml / min, gas space velocity is 150000h -1 , the concentration ratio of NO and NH3 is 1:1.

[0085] Example 5 (5% Pr2O35% WO3-20% CeO2 / SiO2-TiO2)

[0086] (1) 20 ml of water, 100 ml of ethanol, and 30 ml of 28% wt ammonia solution were mixed, 9.4 g of polyethylene glycol was added as a dispersant, and the mixture was stirred at room temperature for 2 h. 9.4 g of tetraethyl orthosilicate was added to the mixed solution, and the mixture was stirred at room temperature for 4 h. The mixture was then filtered, washed with ethanol and water for 3 times until the pH value was 7, and the filter cake was dried in an oven at 110° C. for 12 h to obtain silicon nanocores.

[0087] (2) Grind the silicon nanocore into powder, add it to a solution of 20 ml water, 100 ml ethanol, and 30 ml 28% wt ammonia water, and stir it at room temperature for 2 hours. Add 3.07 g of tetrabutyl titanate to the above mixed solution and stir it at room temperature for 4 hours. Transfer the reaction solution to a stainless steel reactor lined with polytetrafluoroethylene and keep it at 180°C for 16 hours. After the insulation is completed and the temperature drops to room temperature, filter it, wash it with ethanol and water three times to pH 7, dry the filter cake in an oven at 110°C for 12 hours, and then calcine it at 500°C in a muffle furnace for 4 hours (heating rate 2°C / min), and a core-shell structure carrier is obtained, and the mol ratio of SiO2 to TiO2 is 5:1.

[0088] (3) 2 g of the above carrier was ground into powder, added to 14.53 ml of 0.16 mol / l cerium nitrate solution, stirred at room temperature for 4 h, and then dried in an oven at 110° C. for 12 h to obtain a catalyst loaded with active components.

[0089] (4) 2 g of the above carrier was ground into powder, added to 3.59 ml of 0.01 mol / l ammonium metatungstate solution and 15.16 ml of 0.04 mol / l praseodymium nitrate solution, stirred at room temperature for 4 h, dried in an oven at 110°C for 12 h, and then calcined in a muffle furnace at 200°C for 2 h and 400°C for 2 h (heating rate 2°C / min). The supported catalyst was obtained.

[0090] (5) Grind 2 g of the above carrier into powder, add it to a mixed solution of 8 ml of 2-amino-4,4'-biphenyldicarboxylic acid, 16 ml of DMF, and 24 ml of hydrochloric acid, stir it at room temperature for 4 h, filter it, wash it with ethanol and water three times until the pH is 7, dry the filter cake in an oven at 110 ° C for 12 h, and then calcine it at 200 ° C for 2 h and 400 ° C for 2 h in a muffle furnace (heating rate 2 ° C / min) to obtain the final amino-modified core-shell catalyst.

[0091] Test conditions: 500ppm NO, 500ppm NH3, H2O 10%, the rest is air, gas flow rate is 300ml / min, gas space velocity is 150000h -1 , the concentration ratio of NO and NH3 is 1:1.

[0092] Comparative Example 1

[0093] Compared with Example 1, the preparation method of the catalyst is different from that of Example 1 only in that: the amino group is not modified in this comparative example, and the rest of the preparation method and test conditions are the same as those of Example 1.

[0094] Comparative Example 2

[0095] Compared with Example 1, the preparation method of the catalyst is different from that of Example 1 only in that the dispersant is not added in this comparative example, and the rest of the preparation method and test conditions are the same as those of Example 1.

[0096] Comparative Example 3

[0097] Compared with Example 1, the preparation method of the catalyst is different from that of Example 1 only in that this comparative example does not contain the auxiliary agent Pr2O3, and the rest of the preparation method and test conditions are the same as those of Example 1.

[0098] Comparative Example 4

[0099] Compared with Example 1, the preparation method of the catalyst is different from that of Example 1 only in that the comparative example does not contain the auxiliary agent WO3, and the rest of the preparation method and test conditions are the same as those of Example 1.

[0100] Comparative Example 5

[0101] Compared with Example 1, the preparation method of the catalyst is different from that of Example 1 only in that this comparative example does not contain the active component CeO2, and the rest of the preparation method and test conditions are the same as those of Example 1.

[0102] Performance testing:

[0103] The catalytic performance of the catalysts provided in the above examples and comparative examples was tested, and the conversion rate results of catalytic removal of NOx are shown in Table 1 below:

[0104] Table 1

[0105]

[0106] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst for catalytic reduction of NOx, comprising the following components: Carrier: core-shell structure SiO2-TiO2, Active ingredients: CeO2, Additives: Pr2O3 and WO3, Amino groups modified on the catalyst surface; Based on the mass of the carrier, the mass percentage of CeO2 is 4%-20%, the mass percentage of Pr2O3 is 1%-5%, and the mass percentage of WO3 is 1%-5%; the molar ratio of Ti to Si is 1-5.

2. A method for preparing the catalyst according to claim 1, comprising the following steps: (1) uniformly mixing a dispersant, a solvent and an alkali solution, adding a silicon source, filtering, washing and drying to obtain silicon nanocores; (2) grinding the silicon nanocore into powder, adding it to a mixed solution of a solvent and an alkali solution, then adding a titanium source, keeping the mixture warm, filtering, washing, drying, and calcining to obtain a core-shell structure carrier; (3) grinding the core-shell structure carrier into powder, adding the precursor solution of the active component, and drying to obtain a core-shell catalyst loaded with the active component; (4) grinding the core-shell catalyst loaded with active components into powder, adding the precursor solution of the auxiliary component, drying, and calcining; (5) Grinding the product obtained in step (4) into powder, adding it to a mixed solution containing an organic ligand with an amino group, an organic solvent, and an acid, filtering it with suction, washing it, drying it, and calcining it.

3. The method according to claim 2, characterized in that The dispersant in step (1) includes one or more of cetyltrimethylammonium bromide (CTAB), P123, and polyethylene glycol; the silicon source is selected from one or more of ethyl orthosilicate, methyl orthosilicate, silicon tetrachloride, and silicic acid.

4. The method according to claim 2 or 3, characterized in that: The titanium source in step (2) is selected from tetrabutyl titanate and / or titanium tetrachloride.

5. The method according to any one of claims 2 to 4, characterized in that: The calcination temperature in step (2) is 200-600° C., and the calcination time is 2-6 hours.

6. The method according to any one of claims 2 to 5, characterized in that: The calcination temperature in step (4) is 200-600° C. and the calcination time is 2-6 hours.

7. The method according to any one of claims 2 to 6, characterized in that: In step (5), the organic ligand with an amino group is selected from one or more of 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane, 2-amino-4,4'-biphenyldicarboxylic acid, ethylenediamine, and phenylenediamine.

8. The method according to any one of claims 2 to 7, characterized in that: In step (5), the acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and formic acid.

9. The method according to any one of claims 2-3, characterized in that: In step (5), the mass volume ratio of the product obtained in step (4) to the organic ligand with amino group is 1g:2-4ml, the volume ratio of the organic ligand with amino group to the organic solvent is 1:1-2, and the volume ratio of the organic ligand with amino group to the acid is 1:1-3.

10. Use of the catalyst according to claim 1 or the catalyst prepared by the method according to any one of claims 2 to 9, characterized in that: The catalyst is used to catalyze the SCR reaction of NOx; the temperature of the SCR reaction is 100°C to 600°C.

Citation Information

Patent Citations

  • Catalyst for selective catalytic reduction of nitric oxide and preparation method of catalyst

    CN106111183A

  • Core-shell-structured oxide supported Pt catalyst as well as preparation method and application of Pt catalyst

    CN107597104A

  • Catalyst for removing nitrogen oxide

    JP1991270732A

  • Catalyst for cleaning exhaust gas

    JP2010094626A